Essential requirement for RING finger E3 ubiquitin ligase Hakai in early embryonic development of Drosophila. - Kaido, M.; Wada, H.; Shindo, M.; Hayashi, S. (Genes to cells : devoted to molecular & cellular mechanisms, 2009)
Hakai is a RING finger type E3 ubiquitin ligase that is highly conserved in metazoans. Mammalian Hakai was shown to bind and ubiquitinate the intracellular domain of E-cadherin, and this activity is implicated in down-regulation of E-cadherin during v-Src-induced cellular transformation. To evaluate this model in vivo, we studied the function of the Drosophila homologue of Hakai. In cultured S2 cells, Drosophila Hakai and E-cadherin (Shotgun) formed a complex in a way distinct from the interaction described for mammalian counterparts. Hakai null mutants died during larval stages but this lethality could be offset by a HA-tagged Hakai construct. While zygotic Hakai function was dispensable for cell proliferation and differentiation in the wing disc epithelium, maternal Hakai mutants showed a variety of defects in epithelial integrity, including stochastic loss of E-cadherin expression and reduction of aPKC; defects in cell specification and cell migration were also observed. No increase of E-cadherin, however, was observed. Regulation of multiple target proteins under control of Hakai is, therefore, essential for early embryonic morphogenesis in Drosophila.